REVIEW OF IMPLEMENTATION OF CRIMINAL JURIDICAL CRIME AGAINST THEFT WITH VIOLENCE - achmad sulchan (Jurnal Pembaharuan Hukum, 2018)
In the implementation of law enforcement does not always correspond with what is written in the legislation. Law is created, grow and thrive in the community with the aim to regulate people's lives in order to create order, peace, tranquility and prosperity in society. This is reflected from one of the statutory functions as a tool of social control. Related criminal in the theft with violence as stipulated in Article 365 Book of the Criminal Justice Act. Application of the law against the crime of theft with violence shall comply with the applicable substantive criminal provisions and requirements can dipidananya defendant based on the facts revealed in court, there are two valid evidence, sworn testimony of witnesses who based their religion and beliefs of judges in deciding a defendant, to consider things that are burdensome and ease; To achieve the rule of law and the rule of law and justice with dignity, the judge legally consider also that the discovery of things that can release the defendant from criminal liability, either as an excuse or reason pemaaaf, the existence of a fault, is against the law and the absence of any reason as criminal eraser, so the judge can be found sane defendant considered to be able to be responsible